Bioresorbable vascular scaffolds—what does the future bring? - Bil, Jacek; Gil, Robert J. (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
Bioresorbable vascular scaffolds (BVS) have emerged as an interesting alternative since the presence of the prosthesis in the coronary artery is transient. This technology enables to restore the normal vasomotor tone and allows positive remodeling, simultaneously reducing the trigger for persistent inflammation and facilitating further interventions by percutaneous or surgical means. Absorb BVS® is the first generation everolimus-eluting poly-L-lactide (PLLA) bioresorbable scaffold. In recent meta-analyses Absorb BVS® was definitely proved to be safe and effective device in the treatment of symptomatic coronary artery disease. This was recently confirmed by FDA advisory panel of experts who recommended approval of the device based on an analysis of its risks and rewards. Nevertheless, still there are some concerns regarding stent thrombosis, and the real vessel functionality restoration at long-term observation. Worth mentioning is the fact that apart from stable coronary disease Absorb BVS® is used successfully in a series of off-label clinical settings such as acute coronary syndromes including STEMI, in-stent restenosis, coronary bifurcations, left main stenting or chronic total occlusions. Moreover, new bioresorbable scaffolds are under development with DEsolve® and DREAM 2G®, which are the most advanced.